Review: Impact of Food and Climate Change on Pastoral Industries - Uddin, Md E.; Kebreab, Ermias (Frontiers in Sustainable Food Systems, 2020)
The industrialization of agriculture based on inexpensive fossil fuels allowed for unprecedented levels of food production and population growth, but simultaneously contributed to a threat to food systems and population well-being: climate change. This paper analyses the impacts and adaptations available to the world’s pastoral production systems including potential mitigation and adaptation strategies. The current food system is under pressure to satisfy the needs of the increasing population with already limited natural resources particularly land and water, and now increasingly under pressure due to climate change. Increasing incomes from greater number of people have increased demand for animal source foods. As a result, domestic livestock numbers are rising, particularly in low-income countries with greater dependence on pasture for animal feed. The carrying capacity of pastured land is limited; therefore, increasing animal numbers may cause environmental degradation and loss of productivity from pastoral industries. In some countries, the increasing demand has prompted some to burn forestlands and convert them into crop production, and after the land is degraded into pasture mainly for raising large ruminants. Changes in atmospheric carbon dioxide levels and ambient temperatures are predicted to make a number of changes to the growth of herbage for animals. Several strategies can be implemented to optimize the pasture-based food system, including choosing the right breed, improving reproductive efficiency, improving grazing management, and maintaining an animal feed base. The global challenge is to meet our food production needs while sustaining our environment. Producers in all income categories have a role to play in adapting to these challenges.